Autophagy in farm animals: current knowledge and future challenges. Issue 8 (3rd August 2021) - Tesseraud, Sophie; Avril, Pascale; Bonnet, Muriel; Bonnieu, Anne; Cassar-Malek, Isabelle; Chabi, Béatrice; Dessauge, Frédéric; Gabillard, Jean-Charles; Perruchot, Marie-Hélène; Seiliez, Iban
ABSTRACT: Autophagy (a process of cellular self-eating) is a conserved cellular degradative process that plays important roles in maintaining homeostasis and preventing nutritional, metabolic, and infection-mediated stresses. Surprisingly, little attention has been paid to the role of this cellular function in species of agronomical interest, and the details of how autophagy functions in the development of phenotypes of agricultural interest remain largely unexplored. Here, we first provide a brief description of the main mechanisms involved in autophagy, then review our current knowledge regarding autophagy in species of agronomical interest, with particular attention to physiological functions supporting livestock animal production, and finally assess the potential of translating the acquired knowledge to improve animal development, growth and health in the context of growing social, economic and environmental challenges for agriculture. Abbreviations: AKT: AKT serine/threonine kinase; AMPK: AMP-activated protein kinase; ASC: adipose-derived stem cells; ATG: autophagy-related; BECN1: beclin 1; BNIP3: BCL2 interacting protein 3; BVDV: bovine viral diarrhea virus; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; CMA: chaperone-mediated autophagy; CTSB: cathepsin B; CTSD: cathepsin D; DAP: Death-Associated Protein; ER: endoplasmic reticulum; GFP: green fluorescent protein; Gln: Glutamine; HSPA8/HSC70: heat shock protein family A (Hsp70) member 8; IF: immunofluorescence; IVP: in vitro produced; LAMP2A: lysosomal associated membrane protein 2A; LMS: lysosomal membrane stability; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MDBK: Madin-Darby bovine kidney; MSC: mesenchymal stem cells; MTOR: mechanistic target of rapamycin kinase; MTORC1: MTOR complex 1; NBR1: NBR1 autophagy cargo receptor; NDV: Newcastle disease virus; NECTIN4: nectin cell adhesion molecule 4; NOD1: nucleotide-binding oligomerization domain 1; OCD: osteochondritis dissecans; OEC: oviduct epithelial cells; OPTN: optineurin; PI3K: phosphoinositide-3-kinase; PPRV: peste des petits ruminants virus; RHDV: rabbit hemorrhagic disease virus; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscopy.